The State of Special Education in Catholic Schools - DeFiore, Leonard (Catholic Education: A Journal of Inquiry and Practice, 2006)
Catholic educators in recent years have worked to increase their schools’ capacity to provide special education services to more students. The expansion of federal programs to support students with special needs has aided in dealing with this issue, but it has also exacerbated problems. The exacerbation comes from the increased focus on both the needs of children and the inability of the schools to respond positively as often as they would like. The aid comes in the form of some governmental assistance as well as increased financial support from local sources. However, the demand for services continues to exceed the resources available to respond. This paper explores the current dimensions of this situation.